Signal detection of rhabdomyolysis and death for rivastigmine: a pharmacovigilance study - Mahee, Sadique Abdal (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.